Techno-economic feasibility study of tidal power plant with seawater pumped storage in the Philippines - Ibañez, Roderaid T.
The Phiiippine Energy Plan (PEP) 2017-2040 proposes the introduction of new energy harnessing technology such as wave and tidal energy conversion to the national grid by 2030. With this scenario, the study aims to assess the technical and economic aspects of tidal power plant in the Phihppines by exploring different energy storage alternatives. Also, the siting of possible site locations of Seawater Pumped Hydro Energy Storage System (SPSS) is studied due to its site-specific requirements. Using the current available data from National Mapping and Resource Information Authority (NAMRIA), tidal current information and SPSS sites are produced. Out of 47 topographic maps from NAMRIA,there are 65 potential sites for Tidal Power Plant with SPSS. Two cases are made for the simulation, optimization, and assessment using HOMER Pro of tidal power plant system: Off grid and On grid system. For project lifetime of 25 years in Basilan Strait, the Off grid system (Tidal power plant with SPSS) provides levelized cost of electricity (LCOE) and net present cost (NPC) values of 1,532.585 USD/kW hr and 14,388,000 USD. Sensitivity analysis is done to simulate tidal energy system with lead acid and lithium ion batteries. For the Ongrid tidal power plant system, the values of LCOE and NPC are around 0.131111 USD/KW hr and 174,947.3 USD. Sensitivity analysis is also done to observe the change of economic parameters with respect to project lifetime. Other sites with measured tidal current potential are subjected to the same analysis done with Basilan.